2020
DOI: 10.1101/2020.12.17.423041
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A new family of structurally conserved fungal effectors displays epistatic interactions with plant resistance proteins

Abstract: Recognition of a pathogen avirulence (AVR) effector protein by a cognate plant resistance (R) protein triggers a set of immune responses that render the plant resistant. Pathogens can escape this so-called Effector-Triggered Immunity (ETI) by different mechanisms including the deletion or loss-of-function mutation of the AVR gene, the incorporation of point mutations that allow recognition to be evaded while maintaining virulence function, and the acquisition of new effectors that suppress AVR recognition. The… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 70 publications
2
30
0
Order By: Relevance
“…The MAX effector family were originally defined as AVR effectors from M. oryzae and ToxB from P. tritici-repentis [28] but pattern-based sequence searches suggest they are widely distributed amongst the Dothideomycetes [28,48]. Similarly, LARS effectors, defined in Leptosphaeria maculans and Fulvia fulva, have structural homologues predicted in at least 13 different fungal species [30]. For the newly described FOLD effectors, homologues of SIX1 (Avr3), SIX6 and SIX13 are found in many formae speciales of F. oxysporum and are also present in several fungal genera including Colletotrichum, Ustilaginoidea, Leptosphaeria, Pyrenophora and Bipolaris.…”
Section: Expanding the Structural Classes In Fungal Effectorsmentioning
confidence: 99%
See 2 more Smart Citations
“…The MAX effector family were originally defined as AVR effectors from M. oryzae and ToxB from P. tritici-repentis [28] but pattern-based sequence searches suggest they are widely distributed amongst the Dothideomycetes [28,48]. Similarly, LARS effectors, defined in Leptosphaeria maculans and Fulvia fulva, have structural homologues predicted in at least 13 different fungal species [30]. For the newly described FOLD effectors, homologues of SIX1 (Avr3), SIX6 and SIX13 are found in many formae speciales of F. oxysporum and are also present in several fungal genera including Colletotrichum, Ustilaginoidea, Leptosphaeria, Pyrenophora and Bipolaris.…”
Section: Expanding the Structural Classes In Fungal Effectorsmentioning
confidence: 99%
“…The LARS effectors represent another example of effectors that can activate and suppress resistance-gene-mediated immunity. AvrLm4-7 can prevent recognition of AvrLm3 and AvrLm9 (all LARS structural homologues [30]), by their cognate Rlm receptors [75,76]. Rlm9 encodes a wall-associated kinase [77], but the identify of Rlm4, -7 and -3 remain unknown.…”
Section: Effector Structural Classes and Receptor Recognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies showed that some effector protein families share structural similarity rather than sequence similarity with effectors from different fungi 27,28 . Thus the DsCEs were assessed for possible structural similarities to characterised proteins using HHpred.…”
Section: Septosporum Candidate Effectors Have Sequence and Structural Similarity To Fungal Virulence Factorsmentioning
confidence: 99%
“…Avirulent effectors Avr1-CO39, Avr-Pia and AvrPiz-t from M. oryzae and ToxB from the wheat pathogen Pyrenophora tritici-repentis are unrelated by their sequences; however, they share a common β sandwich fold and are together classified as MAX (Magnaporthe Avrs and ToxB-like) effectors (16). Similarly, in phytopathogenic Leptosphaeria maculans, AvrLm3, AvrLm4-7 and AvrLm5-9 are structural analogs belonging to LARS (Leptosphaeria avirulence-suppressing) effectors (17,18). In powdery mildews, such as Blumeria graminis, RALPH (RNase-like proteins expressed in haustoria) effectors, that commonly adopt the structural folds of RNase despite highly divergent sequences, represent a significant portion of the effectorome (19)(20)(21).…”
Section: Main Text Introductionmentioning
confidence: 99%